Converting to Continuity: Temporality and Self in Eastern Orthodox Conversion Narratives. Issue 3 (17th November 2015) - Winchester, Daniel
Abstract : Based on interviews with converts to Eastern Orthodox Christianity in the United States, this article documents and analyzes a narrative form in which conversion is described as the progressive discovery of a latent religious self that was part of one's life all along, or what I term a conversion to continuity. These findings contrast markedly with those of most contemporary conversion research, which emphasize the narration of a dramatic temporal break between converts' past and present religious selves (epitomized by the evangelical "born‐again" genre). I examine how and why temporal continuity was a characteristic feature of these conversion accounts and demonstrate how such narratives helped constitute forms of religious experience and self‐identity that differ in important respects from those documented in previous studies. In light of these findings, I argue for a reconceptualization of continuity and discontinuity within processes of religious identity change as an institutionally anchored figure/ground relationship as opposed to an either/or dichotomy. I also highlight promising avenues for future comparative research on the relationships between time, narrative, and subjectivity across religious and secular contexts.